2015
DOI: 10.3727/096368914x679327
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Alloreactive T-Cells by Anti-CD137-Saporin Immunotoxin

Abstract: Depletion of alloreactive T-lymphocytes from allogeneic bone marrow transplants may prevent graft-versus-host disease (GVHD) without impairing donor cell engraftment, immunity, and the graft-versus-leukemia (GVL) effect. Alloreactive T-cells may be identified by their expression, upon activation, of CD137, a costimulatory receptor and putative surrogate marker for antigen-specific effector T-cells. In this context, we tested the use of anti-CD137-saporin immunotoxin to selectively deplete mouse and human allor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Instead of anti-cancer treatment, RIPs have been also used to eliminate the cholinergic inputs to hippocampus [ 187 ], monocyte-derived inflammatory dendritic cells [ 188 ], and alloreactive CD4 + and CD8 + T-cells through CD137-mediated internalization [ 189 ]. The cholinergic projections to ventral subiculum were selectively eliminated using 192 IgG-saporin conjugates, and this model is useful for investigation of the cholinergic modulation of subicular theta-gamma activity on spatial learning and memory functions in rats.…”
Section: Novel Potential Applications Of Ripsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of anti-cancer treatment, RIPs have been also used to eliminate the cholinergic inputs to hippocampus [ 187 ], monocyte-derived inflammatory dendritic cells [ 188 ], and alloreactive CD4 + and CD8 + T-cells through CD137-mediated internalization [ 189 ]. The cholinergic projections to ventral subiculum were selectively eliminated using 192 IgG-saporin conjugates, and this model is useful for investigation of the cholinergic modulation of subicular theta-gamma activity on spatial learning and memory functions in rats.…”
Section: Novel Potential Applications Of Ripsmentioning
confidence: 99%
“…CD137 signaling is considered to be involved in multiple stages of GVHD development. Lee et al developed a method to selectively eliminate alloreactive CD4 + and CD8 + T-cells through CD137-mediated internalization of anti-CD137 mAbs conjugated with saporin [ 189 ]. CD137-expressing cells were killed by the treatment with the conjugate, and transfer of donor T-cells after allodepletion showed no evident GVHD [ 189 ].…”
Section: Novel Potential Applications Of Ripsmentioning
confidence: 99%
“…However, blockade of CD137 in conditioned recipients reduces either CD8 + T cell-mediated or CD4 + T cell-mediated GVHD lethality (21). Consistently, in a MHC-disparity acute GVHD model, depletion of alloreactive donor CD137 + T cells does not induce the development of GVHD (22). It also has been shown that cardiac allograft rejection is inhibited by anti-CD137L monoclonal antibody in T-cell-replete mice (23).…”
Section: T-cell Costimulationmentioning
confidence: 84%
“…To demonstrate that restored antigen-recognition by B cells, could also result in selective killing of ACPA-expressing B cells, we conjugated the biotinylated antigen variants to a streptavidin-saporin conjugate (SA-ZAP, Figure A and B). , Saporin is a cytotoxic ribosome inhibitor that induces cell death by apoptosis, which has been used in many in vivo studies as antibody-drug conjugate. Equal numbers (1 × 10 4 ) of ACPA-expressing and TT-specific immortalized B cells were cultured with 0, 0.1, 1, 10, and 100 nM antigen-SA-ZAP conjugates. After 4 days of incubation, a XTT cell viability assay was performed to assess the amount of remaining viable cells.…”
Section: Resultsmentioning
confidence: 99%